(untitled) (Journal of Asian Development Studies, 2024)
Infertility can be a significant source of stress, affecting not only individuals but also their relationships and overall well-being. This study examines the relationship between perceived control, marital satisfaction, social support and infertility-related Stress in women seeking fertility treatment. A correlational research design with a non-probability purposive sampling strategy was used. One hundred ten diagnosed infertile women were recruited at age 35 years and above. The Urdu version of all scales was administered for pilot testing to 10 diagnosed infertile women taken from Government hospitals in Lahore. For statistical analysis, SPSS version 26 was used to analyze the data by applying mediated moderation by process macro and independent sample t-test. A total of 110 responses were received. The overall perceived control score was found to be 12.10 ± 6.53, marital satisfaction score of 10.40 ±5.24, social support score of 10.92 ±4.62 and infertility related Stress score of 55.91 ±7.90. Perceived control has a significant impact on infertility-related Stress (β=-.81***). The overall difference in perceived control score (p<0.05) marital satisfaction score(p<0.05) and infertility-related Stress score (p<0.05) in employed and unemployed women was also significant. Overall, perceived control has a direct relationship with marital satisfaction and with infertility-related Stress. The interaction between marital satisfaction and social support (MS*SS) is also significant. Significant employment differences in perceived control, marital satisfaction, and infertility-related Stress were found. Implications for therapeutic interventions and support programs for women facing infertility are discussed, highlighting the need for a holistic approach to mental health and relational well-being in this context.